2018
DOI: 10.12688/f1000research.14476.2
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the higher incidence of tuberculosis among migrants and ethnic minorities in the UK

Abstract: Migrants and ethnic minorities in the UK have higher rates of tuberculosis (TB) compared with the general population. Historically, much of the disparity in incidence between UK-born and migrant populations has been attributed to differential pathogen exposure, due to migration from high-incidence regions and the transnational connections maintained with TB endemic countries of birth or ethnic origin. However, focusing solely on exposure fails to address the relatively high rates of progression to active disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 158 publications
(112 reference statements)
2
24
1
Order By: Relevance
“…Thus, the friendly therapy policy in Taiwan has resulted in an improved experience of reducing structural barriers to TB mitigation since its implementation in 2014, which has successfully promoted the anti-TB treatment outcomes including improvement in treatment initiation especially those who with S− TB or B− TB and increasing treatment completion for those migrants with TB stayed in Taiwan. Therefore, based on our observations, there is a need for intensifying health education that promotes TB therapy includes delivering the information of the ongoing availability of free, accessible health services for vulnerable groups such as high-risk migrants; this health education could also be a critical element in increasing treatment success ( Hayward et al, 2018 ; Scandurra et al, 2020 ; Dangisso, Datiko & Lindtjørn, 2015 ) and early therapy for individuals with TB in receiving countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the friendly therapy policy in Taiwan has resulted in an improved experience of reducing structural barriers to TB mitigation since its implementation in 2014, which has successfully promoted the anti-TB treatment outcomes including improvement in treatment initiation especially those who with S− TB or B− TB and increasing treatment completion for those migrants with TB stayed in Taiwan. Therefore, based on our observations, there is a need for intensifying health education that promotes TB therapy includes delivering the information of the ongoing availability of free, accessible health services for vulnerable groups such as high-risk migrants; this health education could also be a critical element in increasing treatment success ( Hayward et al, 2018 ; Scandurra et al, 2020 ; Dangisso, Datiko & Lindtjørn, 2015 ) and early therapy for individuals with TB in receiving countries.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies revealed that a 30.2% ( Kuan, Yang & Wu, 2014 ) and 14.3% ( Kuan, 2018 ) smear-positive sputum among marriage migrants vs. labor migrants in Taiwan. In term of TB control targeting high TB incidence migrants, it should be taken into consideration along with screening the differences in pathogen exposure due to their origins, the ethnic socio-economic disparities and the experience of migration itself ( Hayward et al, 2018 ); moreover, to overcome the cultural and structural barriers to accessing healthcare ( Hayward et al, 2018 ) is also critical. Thus, a friendly TB therapy policy may prompt access to treatment for a migrant in the new residing country.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding these critical confounding factors is vital to delineate the contribution of BCG-induced immune protection against COVID-19. Effect of immigrant population with childhood BCG vaccination: Some high-income countries, such as the USA, have a significant immigrant population who would have received a childhood BCG vaccination in their country of birth [ 45 , 46 ]. The proportion of such a population would affect the disease transmission and mortality of COVID-19.…”
Section: Implied Effects Of Bcg On the Heterologous Immune Responsmentioning
confidence: 99%
“…Mycobacterium tuberculosis (MTB), the causative agent of tuberculosis (TB) is the leading cause of infectious disease worldwide ( 1 , 2 ), accounting for the deaths of approximately 1.3 million people each year ( 3 ). The United Kingdom (UK) has seen an increase in TB since the late 1980s, with rates higher than the rest of Europe ( 4 ), and there are currently around 6000 new cases each year ( 5 ). In 2016, 73.6% of confirmed TB cases in the UK were foreign-born, with India and Pakistan the most frequent countries of origin ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%